Edukasi Berbasis Literasi untuk Meningkatkan Pengetahuan Masyarakat tentang Khasiat Rimpang Herbal - Siti Uswatun Hasanah; Diki Prayugo Wibowo; Hesti Riasari; Sani Nurlaela Fitriansyah; Irma Erika Herawati (Ilin Institute, 2026)
Medicinal plants can consist of herbs or specific parts of plants, such as spices commonly used in cooking. In today’s digital era, the dissemination of information regarding the use of herbal medicine plays an important role in public education. During the Industry 4.0 era, people can easily access various information independently through websites and online learning platforms. However, the utilization of local herbal plants remains relatively low due to limited public understanding of their potential as medicinal herbs. This community service activity aimed to improve the knowledge and understanding of the residents of Ciburuan Hamlet, Jingkang Village, Bandung Regency, regarding herbal plants, particularly the rhizomes of ginger, turmeric, aromatic ginger (kencur), and galangal (lengkuas). Education was carried out through interactive education sessions and brochure distribution. The methods included preliminary observation, interviews, and questionnaires. The results showed a significant increase in participants’ knowledge about the active compounds and pharmacological activities of herbal plants. Before the activity, most participants were unfamiliar with the bioactive components of herbal rhizomes and only knew their traditional uses. After the interactive session, all participants were able to recognize the chemical constituents and mechanisms of action of these herbs as antioxidants, antibacterials, and anti-inflammatory agents. This activity demonstrates that digital and visual literacy-based education can effectively enhance public awareness (83%) and confidence in using herbal medicine as an alternative for maintaining family health.